Evaluation of Fistulotomy with Immediate Sphincteric Reconstruction in the Treatment of High Transsphincteric Perianal Fistula - Orban,Yasser A. (2021)
Abstract Background High perianal fistula treatment remains challenging, mainly due to the variability in success and recurrence rates as well as continence impairment risks. So far, no procedure can be considered the gold standard for surgical treatment. Yet, strong efforts to identify effective and complication-free surgical options are ongoing. Fistulotomy can be considered the best perianal fistula treatment option, providing a perfect surgical field view, allowing direct access to the source of chronic inflammation. Controversy exists concerning the risk of continence impairment associated with fistulotomy. The present study aimed to assess the outcomes of fistulotomy with immediate sphincteric reconstruction regaring fistula recurrence, incontinence, and patient satisfaction. Methods This interventional study was performed at the General Surgery Department of Zagazig University Hospital during the period from July 2018 to December 2019 on 24 patients with a clinical diagnosis of high transsphincteric fistula-in-ano. The fistulous tract was laid open over the probe placed in the tract. After the fistula tract had been laid open, the tract was curetted and examined for secondary extensions. Then, suturing muscles to muscles, including the internal and external sphincters, by transverse mattress sutures. Results Our study showed that 2 patients develop incontinence to flatus ~ 8.3%.and only one patient develop incontinence to loose stool, 4.2%. Complete healing was achieved in 83% and recurrence was 16.6%. Conclusion Fistulotomy with immediate sphincteric reconstruction is considered to be an effective option in the management of high perianal fistula, with low morbidity and high healing rate with acceptable continence state.